Small molecule inhibitors of the p53-MDM2 protein-protein interaction - Fitzgerald, Ross Patrick (2011)
In Chapter 2, bis- and tris- arylsulfonamides, were investigated as possible inhibitors of the p53-MDM2 protein-protein interaction (PPI). The lead compound, 19, inhibited the PPI, in a fluorescence polarisation (FP) based competitive binding assay with ICso 26.4 pM and the most potent analogue, 66, with ICso 3 μM. The active compounds in this series, possess a 5-chloro-4-nitro-2-sulfonamoyl substituted thiophene ring that is very susceptible to SNAr reactions at the 5-position. Analogues of 19 and 66 were prepared to investigate the SAR of these inhibitors. No improvements in activity or structural activity relationship (SAR) consistent with MDM2 binding were observed and no active analogues without the reactive functionality were found. These compound are no longer being investigated. Chapter 3 describes a 3-D shape-based virtual screening campaign to find new lead compounds. Using queries based on the established Nutlin, benzodiazepine and spiro-oxindole inhibitors, the ZINC database was screened using the program ROCS to find compounds that have good shape similarity (measured by 3D Tanimoto) and similar functional group overlap to the query molecules. 155 compounds were purchased and tested 16 of which inhibited the MDM2-p53 PPI in the FP assay at IC50 ranging between 48.22 and 140.42 1tM. Three analogues, 156,168 and 180, induce low levels of p53 induction in cells using a Luciferese based reporter gene assay with most the potent compound, 180, showed 5.75 fold induction at 8.89 μM. A number of the hit compounds warrant further investigation. Chapter 4 describes the investigation 1.5-benzodiazepiene-2-ones and 1,3-dihydrobenzimidazolin-2-ones as novel scaffolds on which to base potential p53 inhibitors. A small series of analogues of each class were prepared and their ability to disrupt the MDM2-p53 PPI determined using an FP assay. None of the 1.5-benzodiazepiene-2-ones showed any inhibition of the PPI at concentrations up to 500 μM. Some of the 1,3 dihydrobenzimidazolin-2-one based compounds showed low levels of inhibition with the most potent analogue, 214 having IC5o 196.18 PM. These inhibitors showed some SAR based on the size of substituents and the presence of a 6-chloro substituent that has been shown to considerably enhance the activity in other classes of inhibitor. Compounds of this type warrant further investigation using a more diverse compound library.